Effects of foliar and root application of silicon on rice blast fungus in MR219 rice - Ashtiani, Farnaz Abed (2012)
Rice blast caused by fungus Magnaporthe grisea (Hebert) Barr [teleomorph]Pyricularia oryzae Cavara is among the most devastating diseases of rice worldwide. In modern agricultural practices it is highly important to manage diseases and pests using efficient methods with minimum harm to the environment. Although silicon has been reported to significantly reduce foliar diseases in crops, its application has not been widely adopted in Malaysia. Hence studies were conducted to determine the effects of silicon on Pyricularia oryzae. Rice variety MR219 was grown in the glasshouse and the function of silica gel and sodium silicate in conferring resistance against blast was investigated. Silica gel was applied to soil prior to planting (0, 60, 120, 180 g/5 kg of soil) while sodium silicate was used as foliar spray (0, 1,2, 3 mL/L). The treatments were arranged in a completely randomized design with three replications. The severity of disease and silicon content of leaves were compared between the non-amended controls and rice plants receiving the different rates and sources of silicon. Silicon at all rates of application significantly (α=0.05) reduced the severity of disease with the highest reduction (75%) recorded in treatments receiving 120 g of silica gel. The relationship between leaf blast severity (Y) and amount of silicon applied to the plants (X) could be explained by the exponential decay curve using equation y=Ae-bx indicating that leaf blast severity was lower with higher rates of silicon application. Scanning Electron Microscopic observations showed that there were two types of silicified cells on the adaxial surface of rice leaves which included dumbbell-shaped and small scattered silica cells. The X-ray spectra analysis demonstrated a significant difference in weight concentration of silicon in silica cells on the leaf epidermis between silicon treated (25.79%) and non treated plants (7.87%) as well as among plants treated with different rates of silica gel and sodium silicate, indicating that silicon-fertilization resulted in higher deposition of silicon in both kinds of silica cells. Application of silicon also led to a significant increase (25.3 g/kg) in silicon content of leaves compared to nontreated plants (6.28 g/kg). The rate of photosynthesis of silicon treated plants (11.98 μmolm-2s-1) was significantly higher than plants in the control group (6.36 μmolm-2s-1). Shoot dry weight of rice plants increased significantly (1.50 g) with silicon fertilization as compared to non-treated plants (0.90 g). Contrast procedures indicated higher efficiency of silica gel in comparison to sodium silicate in almost all parameters assessed. The results suggest that mitigated levels of disease were associated with fortification of rice leaf epidermal cells through silicon fertilization. Although both foliar and root application of silicon were effective in decreasing the intensity of blast,greater effectiveness was achieved through root application. In conclusion,the study supports the hypothesis that silicon is able to confer resistance against blast disease. This could make silicon a useful tool for managing rice diseases, possibly in conjunction with reduced rate of fungicide, and may provide alternative to rice growers in areas where blast resistant cultivars have become susceptible.